The advantages of distance learning technologies: students’ and university lecturers’ views - A. I. Nazarov; O. V. Sergeeva (Открытое образование (Москва), 2016)
The aim of the research is to analyze the results of the implementation of network education module in Physics into the bachelor education process, which is carried out with the use of distance learning technologies and e-learning platform Blackboard.In accordance with the Federal Law «On Education in the Russian Federation» at the present stage the organization of educational process for bachelors of engineering specialties of the University may be carried out through an integrated combination of traditional full-time study with the possibilities of distance learning technologies.In order to realize the benefits of such an education the authors of the article have been already using e-learning platform Blackboard for four years. On the basis of e-learning platform Blackboard a number of network educational modules with the integrated point-rating system of assessment of learning outcomes were created. In order to improve the educational process, organized with the use of distance learning technologies, and making any necessary adjustments, the students were surveyed and the results obtained in the last two years were analyzed on the basis of the course of physics. The sample was made for those students who studied the course «Mechanics and Molecular Physics» at the Mining and Geology Faculty of Petrozavodsk State University. The comparison of the survey results with objective data obtained with the help of e-learning platform tools was made.The results of the research have shown, that it was possible to organize the systematic work of students during the semester on all proposed educational activities, to provide the students with self-study opportunities in the course of the semester, to motivate students to study physics, as well as to reduce the number of underachieving on this academic discipline. The use of point-rating assessment system was highly appreciated by the students and allowed to implement personality-oriented approach to learning, which combined motivation, ability to select individual educational paths and self-esteem.The results have allowed to carry out the feedback between the subjects of innovative educational process, looking at it organization by the eyes of students and university lecturers. This has confirmed the correctness of the chosen approach to the complex organization of the educational process with the use of e-learning platform, network educational module «Mechanics and Molecular Physics» and point-rating assessment system.On the basis of the results of the responses to the questionnaire and the results of students’ work with a network educational module, designed on the Blackboard e-learning platform, necessary adjustments have been implemented into the educational process and in the proposed means of assessment. It is advisable to continue working in this direction, summarizing learning outcomes for all engineering bachelor students.